Identidad corporativa para el fortalecimiento turístico de la parroquia Salinas, de la ciudad de Guaranda, provincia Bolívar, año 2024 - Coello Camacho, Pedro Luis (2024)
Background: The Parish of Salinas, located in the province of Bolívar, has tourism potential supported by its natural, cultural, and community wealth. However, its tourism development has been limited due to the lack of a well-managed corporate identity. Objectives: To strengthen tourism in the parish of Salinas through the design of a corporate identity. Methodology: Both qualitative and quantitative methods were combined. Direct observations and interviews with local stakeholders were conducted to obtain a detailed understanding of the current situation, along with the review of relevant documents. For quantitative data collection, structured surveys were applied to tourists and residents to capture their perception of Salinas' corporate identity. Results: Despite the region's rich tourism potential, it faces significant challenges in terms of visibility and recognition. The lack of a clear corporate identity has limited its tourism development. Essential values and attributes of Salinas, such as its cultural authenticity, natural wealth, and hospitality, were identified. Based on the analysis, key strategies are proposed, including the creation of a distinctive logo, a representative slogan, the development of a brand manual, and a social media communication campaign. Conclusion: Implementing a coherent and well-managed corporate identity can have a significant impact on Salinas' tourism development, improving its image, increasing its tourism appeal, and strengthening its market position.